Level of Analysis Problem in the Post-Cold War Deterrence: The Need for Regional Perspectives - Mehmetcik, Hakan (Journal of Regional Security, 2018)
The end of the Cold War has had profound effect on deterrence theory and practice. Contrary to the perceived belief that deterrence was a dead concept after the demise of the Cold War rivalries, it lives, even grabs more attentions with recent developments in international relations. During the entire Cold War period, deterrence had been studied within a systemic context in which nuclear superpowers operated in a bipolar world. In the post-Cold War era, with a renewing interest in deterrence theory and practice, deterrence at regional level appears to be more pertinent to new security environment. However, current literature on the concept does not pay adequate attention to deterrence at this level. In this sense, Regional Security Complex Theory(RSCT) has an important explanatory power for resolving regional dynamics in which deterrence practice is generally shaped. This article aims to bridge the gap between deterrence studies and regions, as a level of analysis, by integrating RSCT within the wider deterrence discussion.